To Critique Crisis Communication as a Social Practice: An Integrated Framework - Wang, Huabin (Frontiers in Communication, 2022)
Recent years have witnessed a flourishing development in the field of Public Relations (hereinafter as PR), which adjusts its scholarly attention from the quantitatively inclined studies on behavioural effectiveness to more of a critical discussion about social power and ideological influence within PR practice, consequently in favour of an interpretivist approach with a qualitative methodology towards a holistic analysis of a series of PR performances. Driven by the rise of this critical perspective in qualitative PR research, this paper aims to argue for a critical PR approach, tentatively by integrating a linguistic perspective from Critical Discourse Studies to discuss crisis communication as a social practice. Technically drawing on the theories of Political Public Relations (PPR in short) and Critical Discourse Studies, the proposed framework attaches equal importance to ideology, power, and identity instead of merely management function. It is illustrated that a critical investigation of PR performances approaches both media and institutional discourses, which are constructed by different social actors to frame a crisis and issue immediate responses, exercise its power control and maintain stakeholder relationships, and ultimately restore media and institutional images. On the one hand, the embedded ideologies enacted by the institutional control the media power and construct positive image representations. On the other hand, in order to exercise its administrative control, the institution must emphasise the need for all the stakeholders and the affected group to devote to resolving the crisis. The paper then concludes that the integrated framework together with the qualitative method of linguistic analysis offers PR scholars insights into the relationship between discourse, ideology, and crisis communication, as well as proposes implications on the interdisciplinary research from which general qualitative researchers could benefit. Hopefully, this integrated approach to crisis communication will contribute to broadening the research scope of analysing communication as a social practice towards a comprehensive model.